Qurʾānic Symbolism of the Eyes in Classical Azeri Turkic Poetry - Gasimova, Aida (Oriens, 2015)
The paper examines the intertextual use of Qurʾānic text in the depiction of facial features, specifically in the Ṣūfī symbolism of the eyes in classical Azeri Turkic Ṣūfī poetry—the unique literary tradition which has not yet received its deserved attention in Western scholarship. First, the linguo-historical and geographical boundaries of this tradition are outlined, with a view to accentuating its position among other Turkic traditions. Then the roots of the widespread concept of the manifestation of the divine being and holy scripture in the human face will be traced from their origins in ancient physiognomy and mythology through into the teaching and philosophy of pre-modern Ṣūfī thinkers. The research reveals about fifty Qurʾānic motifs employed in the poetry of a pleiad of poets, Qāḍī Burhānuddīn (d. 800/1398), ʿImāduddīn Nesīmī (d. 820/1417–18), Mīrzā Jihān Shāh Ḥaqīqī (d. 871/1467), Niʿmatullāh Kishwarī (IXth–Xth/XVth–XVIth centuries), Ḥabībī (d. 926/1520), Shāh Ismāʿīl Khaṭāʾī (d. 930/1524), and Muḥammad Fuḍūlī (d. 963/1556), for the depiction of the eyes, a great portion of which is discussed throughout this paper. I argue that the richness and embellishment of the eye images like eye-god, eye-man, eye-heart, eye-murderer, eye-magician, eye-scribe are owing to the eye’s compound structure which include eyelashes, eyelid, pupil, sclera, as well as its function, motion, and associated elements like tears and glances.